"Music for raising awareness, music for joy", dealing with disability at the Secondary School - Pablo Ramos Ramos; Salvador Astruells Moreno (Universidad de La Rioja, 2016)
We describe and analyze the results of the project "Music for raising awareness, music for joy", developed by the music department of the Joan Coromines Secondary School. The main objective was to bring disability's reality to teenagers through the direct contact with disable people and through emotional implication. The participants in the project were both a group of low-academic- performance teenagers and a group of adult disabled people. The cooperative work between both groups culminated with the recording of "The rap of disability".